Analýza vlivu rozměrů čerpacích kanálů při konstrukci nové verze scintilačního detektoru - Kryll, Josef (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2016)
Cílem této práce je nastudovat tématiku environmentální elektronové skenovací mikroskopie a čerpání plynu pro vytvoření vakua v nově navrženém scintilačním detektoru. Dále vytvořením modelu navrženého detektoru a simulací a analýzou proudění plynu v diferenciálně čerpané komoře detektoru a porovnáním výsledků se stávajícím modelem detektoru. Teoretická část je věnována elektronové mikroskopii, zdrojům elektronů a detektory sekundárních elektronů. Dále typy signálů, které se vytvářejí při interakci elektronového svazku se vzorkem. V této části je také věnována pozornost rovnicím popisujícím proudění v popisované komoře a dopad změny rozměrů na vlastnosti sledovaného detektoru. Praktická část se skládá z vytvoření modelu scintilačního detektoru a analýzy proudění plynu s následným porovnáním výsledků se stávající verzí detektoru. Výstupem této práce je model navrženého detektoru s vizuálními výsledky.

The aim of this thesis is to study the issue of eniveromental scanning electron microscopy and pumping gas to create a vacuum in the newly designed scintillation detector. Further, creating a model of recently proposed scintillation detector and simulating and analyzing pumping gas in differentially pumped chamber of detector and the results compare with the previous model. The theoretical part deals with electron microscopy, electron sources, electron optics and secondary electrons detectors. It is also presented which signals are generated by the electron beam on the surface of a solid. Further fluid flow issues and equations describing the flow in the solved chamber are dismantled. Furthermore, the impact of gaseous environment on the trajectory of primary electrons, because there are collisions of primary beam with atoms and molecules of gas. The following section discusses creating, quality and importance of the network in mathematical modelling. A method of a final volume used to calculate the differential equations describing the flow of gas at the premises of the microscope is described . The practical part consists in creating a model of scintillation detector and analyzing the gas flow in drawing a vacuum in the newly designed scintillation detector. Furthermore, the simulation results are compared with the results of simulations on the older type of scintillation detector. The output of this thesis is model of recently proposed scintillation detector with visualized simulation results.
Analysis of the dimensions of pumping channels in a new design of a scintillation detector
Keywords: Elektronová mikroskopie; scintilační detektor; diferenciálně čerpaná komora; modelování proudění tekutin; metoda konečných objemů; Electron microscopy; scintillation detector; differentially pumped chamber; the fluid flow modelling; finite volume method